2001
DOI: 10.1071/ar00003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of partial rust resistance in faba beans

Abstract: Five parent populations of faba bean, differing in reaction to rust disease, were crossed to prepare a complete diallel of F1 hybrids. Detached leaves of the parents and F1 hybrids were challenged with 3 Australian rust populations and symptom development was monitored from 11 to 16 days after inoculation, using a disease score related to the percentage of leaf area covered with pustules, and a nominal value for pustule size. Additive gene action was very important in determining the response to rust disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Macroscopical components of this partial resistance are characterized by reduction in both lesion size and infection frequency, a longer latency period and absence of necrosis Rashid & Bernier, 1986a,b, 1991Sillero et al, 2000). Information on the genetic basis of the slow-rusting resistance is still scant and both nuclear and cytoplasmic genes have been suggested to be responsible (Stoddard & Herath, 2001). However, identified 3 race-specific genes for partial resistance, two of them against race 1 and the other one against race 3.…”
Section: Rustmentioning
confidence: 96%
See 1 more Smart Citation
“…Macroscopical components of this partial resistance are characterized by reduction in both lesion size and infection frequency, a longer latency period and absence of necrosis Rashid & Bernier, 1986a,b, 1991Sillero et al, 2000). Information on the genetic basis of the slow-rusting resistance is still scant and both nuclear and cytoplasmic genes have been suggested to be responsible (Stoddard & Herath, 2001). However, identified 3 race-specific genes for partial resistance, two of them against race 1 and the other one against race 3.…”
Section: Rustmentioning
confidence: 96%
“…Although chemical control of this disease has been reported (Williams, 1978;Gaunt, 1983;Yeoman et al, 1987;Marcellos et al, 1995;, it is obvious that other cost-effective and environmentally friendly alternatives to the extensive use of fungicides should be provided. On the other hand, the use of biological control (Gaunt, 1983) or systemic induced resistance (Murray & Walters, 1992;Rojas et al, 2004) and cross protection (Yarwood, 1956) is not yet viable at the commercial level (Stoddard & Herath, 2001). The use of genetic resistance is considered the most practical and efficient method for the control of this disease.…”
Section: Rustmentioning
confidence: 98%
“…Rust (Uromyces spp. ) resistance in other legumes also shows the involvement of one, two, or three oligogenes, and even polygenes (Stavely, 1984;Edington et al, 1994;Habtu & Zadoks, 1995;Sayler et al, 1995;Kumar et al, 2001;Stoddard & Herath, 2001). Abusaleha et al (1987) reported absence of linkage of pea rust resistance with the flower and stipule base pigmentation.…”
Section: Introductionmentioning
confidence: 92%
“…is the causal agent of faba bean rust, a disease found worldwide that can cause up to a 70% loss in yield, particularly when the infection starts early in the season. Several methods for rust control have been developed, including biological control (Gaunt 1983), systemic induced resistance (Murray and Walters 1992;Sillero 1999) and cross protection (Yarwood 1956), but these have proved to be inapplicable at the commercial level (Stoddard and Herath 2001). Chemical control of the disease has been reported (Williams 1978;Gaunt 1983;Yeoman et al 1987;Marcellos et al 1995;, but the extensive use of fungicides is not desirable in sustainable production systems of grain legumes where the most efficient use of chemicals is pursued.…”
Section: Introductionmentioning
confidence: 99%